Character Building of the Young Generation Through Participation in the Islamic Organizations IPNU and IPPNU in Bangeran Village, Dukun, Gresik - Husnah, Siti Halimatul; Ni’mah, Khoirotun; Ayu, Intan (Al-Ulum: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the role of the Ikatan Pelajar Nahdlatul Ulama (IPNU) and Ikatan Pelajar Putri Nahdlatul Ulama (IPPNU) organizations in the development of Bangeran Village, Dukun District, Gresik Regency. The research employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation, then analyzed using triangulation techniques to ensure data validity. The findings show that IPNU and IPPNU play a significant role in the development of youth character and contribute to various development programs at the village level. These organizations not only focus on character education but also improve the quality of education, skills, and leadership among students. Factors influencing the effectiveness of IPNU-IPPNU in village development include effective leadership, active member participation, and partnerships with various stakeholders. Overall, this study concludes that the existence of IPNU-IPPNU has proven to provide a real contribution in shaping a high-quality young generation while supporting sustainable village development. Therefore, the role of these student organizations needs to be continuously strengthened to become strategic partners in community development and education.